STUDENTS’ SELF-REGULATED LEARNING AT THE FOURTH SEMESTER FOR WRITING PERFORMANCE IN ENGLISH EDUCATION DEPARTMENT AT UIN ALAUDDIN MAKASSAR - Isfani, Aini Nur; Siti Azisah,; An Nur, Muhammad Jabal (English Language, Linguistics, and Culture International Journal, 2022)
This research addresses issue of self-regulated learning in students writing performance for the fourth semester of English Education Department at UIN Alauddin Makassar. The research objectives are to find out the students’ who have Self-Regulated Learning in doing Writing Assignment for the fourth semester students’ of English Education Department at UIN Alauddin Makassar, and addition to find out do Self-Regulated Learning influence students’ Writing Performance in English Education Department at UIN Alauddin Makassar. The method of this research used qualitative method. The subjects of this research were thirty two (32) students of English Education Department at UIN Alauddin Makassar academic year 2018 which taken by using purposive sampling. The data of this research is obtained from semi structured interview instrument with supporting data from questionnaire. The data analysis techniques in this research used three steps, i.e. reading/memoing, describing and classifying. The result shows that the experience Self-Regulated Learning can organize and control the learning schedule according to the priority scale and plan each learning activity where the student's metacognition will work when he obeys the plan he made. In self-regulated learning there is motivation in which students really need the role of motivation from both a person and the environment. With the existence of self-regulated learning and contributed learning environment can improve and structured learning outcomes behavior in order to get good achievement.